Personal Branding Influencer pada Media Sosial Tiktok (Studi Kasus pada Akun @veliaveve) - Octavianus, Abraham; Oktavianti, Roswita (Koneksi, 2022)
Tiktok is a social media platform where people can enjoy watching videos or content. People who work on making videos or this content are referred to as content creators or influencers. An influencer is not only always required to provide creative ideas in each content but also needs to build a good self-image in the eyes of the public, commonly called personal branding. It is the basis of this research, namely how an influencer creates personal branding. According to Peter Montoya, eight concepts make up personal branding: specialization, leadership, personality, difference, visibility, unity, constancy, and good name. Seeing the correlation between personal branding and influencers, the researcher chose Velia as the research subject. Velia herself manages the @veliaveve account, which is her account and now has 1.4 million followers on the Tiktok channel. The formulation of the problem in this study is how personal branding influencers on Tiktok social media are. Researchers tried to examine Velia's account using a qualitative case study method approach. The results of this study also state that it is essential to understand personal branding in terms of being an influencer. The exciting thing about these eight concepts is the concept of a good name. Influencers maintain a good name by building relationships with their followers by replying to comments or going live so they can communicate directly. Tiktok merupakan platform media sosial dimana pengguna menikmati tontonan berupa video. Orang yang bekerja membuat video atau konten ini disebut sebagai content creator atau influencer. Influencer dituntut memberikan ide-ide kreatif dalam tiap kontennya. Seorang influncer juga perlu membangun citra diri yang baik di mata masyarakat atau disebut personal branding. Hal ini yang menjadi dasar penelitian ini yaitu bagaimana cara seorang influencer menciptakan personal branding di media social Tiktok. Menurut Peter Montoya terdapat delapan konsep pembentuk personal branding yaitu, spesialisasi, kepemimpinan, kepribadian, perbedaan, terlihat, kesatuan, keteguhan, dan nama baik. Peneliti memilih Velia sebagai subjek penelitian. Velia sendiri mengelola akun @veliaveve di mana akun tersebut adalah akun pribadi miliknya yang sekarang memiliki 1,4 juta pengikut di kanal Tiktok. Peneliti menggunakan pendekatan penelitian kualitatif dengan metode studi kasus. Hasil dari penelitian ini menunjukkan bahwa menjadi influencer perlu mengerti konsep personal branding. Hal yang menarik dari delapan konsep ini terdapat pada konsep nama baik. Cara influencer dalam menjaga nama baik yakni dengan membangun relasi dengan para pengikutnya seperti membalas komentar, dan melakukan live untuk berkomunikasi secara langsung dengan pengikut.